Does simultaneous bilateral total joint arthroplasty increase deep infection risk compared to staged surgeries? A meta-analysis. Issue 2 (February 2019) - Xu, C.; Qu, P.; Deng, T.; Bell, K.; Chen, J.
Summary: Background: Several studies have compared the incidence of periprosthetic joint infection (PJI) between simultaneous bilateral total joint arthroplasty (SBTJA) and staged bilateral total joint arthroplasty (StBTJA) patients following primary total joint arthroplasty. However, these studies lacked statistical power. Aim: To determine by meta-analysis whether SBTJA increases deep infection risk compared to StBTJA. Methods: All studies were retrieved from PubMed, Embase, Cochrane Library databases, Web of Science, PEDro, CINAHL, SPORTDiscus, and Scopus. A meta-analysis was conducted to compare PJI rate between SBTJA and StBTJA patients. Findings: Overall, there were 16 studies with 36, 765 patients who underwent SBTJA and 71, 558 patients who underwent StBTJA. The pooled data showed that the PJI rate of SBTJA was lower than that of StBTJA (0.84% vs 1.57%; odds ratio (OR): 0.57; 95% confidence interval (CI): 0.49–0.66; heterogeneity, I 2  = 0%; P  = 0.74). In subgroup analysis, the pooled data revealed that there was no significant difference between SBTJA and StBTJA groups for PJI if the two groups had similar baseline demographics (four studies; OR: 0.55; 95% CI: 0.21–1.40; heterogeneity, I 2  = 0%; P  = 0.77). The pooled data showed that the PJI rate of SBTJA patients was comparable with that of StBTJA patients within a three-month staging interval (three studies; OR: 1.22; 95% CI: 0.38–3.88; heterogeneity, I 2  = 0%; P  = 0.42). Conclusion: SBTJA does not increase the risk of subsequent PJI compared to StBTJA. Further studies are needed to provide higher quality evidence to evaluate the two modes of procedure.